"Somebody else's business": The challenge of caring for patients with mental health problems on medical and surgical wards. Issue 4 (9th February 2020) - Foye, Una; Simpson, Alan; Reynolds, Lisa
Accessible summary: What is known on the subject?: People with mental health problems have higher rates of physical health concerns and hospital admissions than those without mental health problems. These patients have poorer outcomes from surgery and have worse experiences of care when admitted for medical or surgical procedures. What the paper adds to existing knowledge?: This paper looks to understand why care may be poorer for patients with mental health problems by speaking to staff providing care in these settings. We spoke to 30 general hospital staff about mental health on the wards and found that a lack of leadership and ownership for prioritising mental health led to people not seeing it as their job, and that it was somebody else's business to manage that side of care. We also found that the emotional effect of caring for people who had attempted suicide or had self‐harm injuries was difficult for staff, impacting on staff well‐being and leading them to distance themselves from providing care in those cases. What are the implications for practice?: There is a need for staff to be supported from the top‐down, with management providing clear leadership around issues and pathways for mental health needs so they know the best way to provide care and encourage collaborative working. In addition, bottom‐up support is needed to help staff personally manage their own well‐being and mental health, including supervision and debriefing from mental health specialists to improve understanding from the patient's perspective and to provide emotional support to manage difficulties. Relevance Statement: This paper places focus on the care of patients with mental health problems in medical and surgical care settings highlighting the interplay between mental and physical health from a perspective that is less often explored. This paper provides insights into the multidisciplinary nature of nursing and the need for integrated care. This provides findings that build a picture of how mental health nursing specialism is needed beyond psychiatric wards and within medical and surgical settings. Abstract: Introduction: Evidence shows that patients with mental health problems have poorer physical health outcomes, increased mortality and experience poorer care during surgery and medical admissions. Issues related to lack of training, stigmatizing attitudes, fear or hopelessness may help understand these poor outcomes. Aim: To explore the experiences of staff in providing care for people with mental health problems. Method: A qualitative service evaluation approach was used. Participants working in an acute care hospital in inner‐city London were recruited across professions and job levels using a self‐selection sampling method. A total of 30 participants took part in semi‐structured interviews ( n = 17) and two focus groups ( n = 13), and data were thematically analysed. Relevant organizational documents and service use data were utilized to inform the evaluation. Results: Key themes were organized across the macro, meso and micro levels to understand the levels of disconnection and silence around mental health in acute care. Themes include systemic factors surrounding the institutional culture, ward cultures and collaborative working, and individuals' sense‐making of mental health and personal well‐being. Implications for practice: These findings signpost the growing need for greater mental health nursing input on medical and surgical wards and within these teams to provide informed knowledge, support and supervision.